Control of Gene Function in Bacteriophage T4: I. Ribonucleic Acid and Deoxyribonucleic Acid Metabolism in T4rII-Infected Lambda-Lysogenic Hosts - Sauerbier, Walter (1969)
Deoxyribonucleic acid (DNA) synthesis in T4rII-infected, lambda-lysogenic strains of Escherichia coli proceeds with one-half the rate of T4 wild-infected bacteria and stops 16 min after infection at 37 C. The rates of ribonucleic acid (RNA) synthesis, however, are the same with T4rII and T4 wild. The turnover of pulse-labeled RNA is slow in K strains (half-lives 10 to 20 min) as compared with B strains (half-lives 2.5 to 6 min). Lambda-lysogeny increases the apparent messenger (m) RNA half-lives in pulse-chase experiments. The shutoff of host RNA synthesis in T4rII infected K(λ) is incomplete. Moreover, the preferential transcription of T4 DNA ceases 13 min after infection, and transcription of host and prophage λ DNA is resumed. The T4 RNA synthesized in rII-infected K(λ) contains no late T4 mRNA. The early portion of the T4 genome, however, is transcribed completely. The T4-induced early modification of bacterial RNA polymerase does occur. Resumption of host DNA transcription at 13 min after infection is not associated with a reversal of the above polymerase modification. It is concluded that in lambdalysogenic bacteria T4rII infections are abortive because RNA polymerase is prevented from transcribing late T4 genes.